Numerical investigation on combustion and emissions in a direct injection compression ignition engine fuelled with various hydrogen–methane–diesel blends at different intake air temperatures. (November 2021) - Mansor, Mohd Radzi Abu; Mohamad, Taib Iskandar; Sabah, Osama
Abstract: Blending hydrogen and methane with diesel in compression ignition engines has been proven to improve both performance and emissions. This work further explores the combustion characteristics and emissions of a direct injection compression ignition (DICI) engine fuelled with various blend ratios of hydrogen, methane and diesel with respect to varying intake air temperatures, as the blend ratio can affect the mixture formation process in such high-speed in-cylinder phenomena. A numerical study using ANSYS Fluent was conducted based on a 0.406-litre Yanmar L100AE-D single-cylinder DICI engine running at 1500 rpm and was verified with a physical experiment using the same engine. The tri-fuel blend consisted of 60% diesel by mass with the remaining 40% made up with various ratios of hydrogen and methane (0%/40%, 12%/28%, 20%/20%, 28%/12%, and 40%/0%). The intake air temperatures were varied at 303 K, 318 K and 338 K, representing near-standard, high and extremely high ambient air temperatures, respectively. The results showed that the presence of methane and hydrogen in diesel fuel resulted in a higher in-cylinder pressure, temperature and heat release rate (HRR). Increasing the intake air temperature caused a proportional increase in the in-cylinder temperature, pressure and HRR. However, the presence of methane lengthened the ignition delay, while increasing hydrogen reversed the trend. While the presence of hydrogen–methane reduced the overall CO emissions, the effect of hydrogen on CO reduction was dominant. In addition, the presence of hydrogen–methane led to an increase in NOx emissions due to the high combustion temperature. The study suggested that an optimized intake temperature and the balanced use of tri-fuel in a direct injection compression ignition engine can significantly improve engine performance and emissions.